THE EFFECTS OF GRDP AND FOREIGN DIRECT INVESTMENTS ON REGIONAL INEQUALITY IN EASTERN INDONESIA - Dina Solehati; Dicky Iranto (Econosains Jurnal Online Ekonomi dan Pendidikan, 2020)
Equity is the goal of the process of economics development. Equity in economic development can be seen from decline in regional inequality. Regional inequality in Eastern Indonesia is quite high and has increased every year. Regional inequality can be calculated from williamson index. This research aims to determine the effects of GRDP and foreign directs investment on regional inequality in Eastern Indonesia period 2010- 2017. This research used pooled data from 12 Provinces in Eastern Indonesia period 2010- 2017 with fixed effects model. The results are GRDP has negative and significant on regional inequality, and foreign directs investment has positive and significant on regional inequality.